Cultural and economic reproduction in education: Essays on class, ideology and the state - Apple, Michael W. (London Routledge, 2017)
First published in 1982, this collection of essays provides an analysis of education$1 (Bs contradictory role in social reproduction. It looks at the complex relations between the economic, political and cultural spheres of society, both historically and at the time of publication, and hones the wider range of debate in on education. This volume will be of interest to those studying sociology and equality in education.s